Prevalence and Factors Associated with Betel Quid Chewing among Adolescent Population: Nattalin Township, Bago Region, Myanmar: A Cross-sectional Study - Kyawt Kyawt Saing; Kay Thi Lwin; Thein Hlaing (Research Highlights in Disease and Health Research Vol. 9, 2023)
The aim of this study was to find out the prevalence and to identify the factors associated with betel quid chewing practice among the adolescent population. Betel quid (BQ) chewing are ancient practices followed by an extensive proportion of the world’s population. These practices are endemic in larger parts of South and Southeast Asia and selected Western Pacific countries. The prevalence of these habits varies across regions, ages, gender, cultural practice, and socioeconomic status groups. A cross-sectional quantitative (primary) study was conducted on 160 adolescents (10-19 years) in Nattalin Township in Myanmar using an interview-structured questionnaire from February 2020 to May 2020. Using SPSS statistical software, simple descriptive statistics (frequency and percentage, mean, median and standard deviation) was done to describe the participating adolescents’ socio-demographic characteristics, knowledge, attitudes and practices. A Chi-square test was performed to determine which factors are statistically associated with betel chewing habits among the study adolescents by considering the P-value (0.05) and significance at <0.05. The prevalence of betel quid chewing adolescents was 28.2% of the total sample (n=160). The betel quid chewer group contained more males than females. The earliest age of starting betel quid chewing was 6 years old. Socio-demographic characteristics included age (equal or more than 15 years) (p<0.001), male (p<0.001), rural residence (p=0.009), a working group (p<0.001), pocket money of more than 10000 kyats (p<0.001), having betel quid used family members (p=0.017) and betel quid used close friends (p<0.001) and the negative attitude (p=0.006) toward betel quid chewing were the factors significantly associated with betel quid chewing practice in this study. The other individual and social factors included education, marital status, parent’s education, parent’s occupation, having BQ chewing father and mother and the environmental factor which was a discussion about BQ chewing and health hazards within 6 months were not significant. The commonest reason for BQ chewing given by the adolescents in this study was peer pressure and the second common reason was curiosity. There is no association between the knowledge and attitude levels of the adolescents. The need for strong behavioural change health promotion programmes that emphasise the risks of betel quid chewing habits for adolescents, as well as more efficient anti-betel quid chewing interventions, must be developed nationally.